Sovereign Wealth Funds and the Quest for Sustainability: Insights from Norway and New Zealand - Benjamin J. Richardson (Nordic Journal of Commercial Law, 2011)
An impressive trend in global financial markets is the growth of sovereign wealth funds (SWFs), some of which purport to invest ethically by considering the social and environmental impact of their financing. Yet, like private investors, these funds primarily view themselves as financial institutions interested in enhancing investment returns. A significant tension, therefore, may emerge between the ethical and financial expectations of SWFs. This article investigates two contrasting cases, the Norwegian Government Pension Fund - Global (NGPF-G) and the New Zealand Superannuation Fund (NZSF), in order to evaluate how they address any tensions between being both virtuous and prosperous. These SWFs have legislative mandates to invest ethically, and have been hailed by some researchers as having among the most progressive approaches in this area.1 But neither fund yet manages its entire portfolio comprehensively to promote sustainable development. Increasingly, nation-states are establishing SWFs in a trend that seemingly defies an era in which many governments have sought to deregulate or otherwise limit their hand in the market.2 In their governance, formally SWFs are public institutions but functionally they are generally expected to be private actors. They invest large pools of state-owned assets in the market to meet macro-economic policy objectives,3 such as to buffer the sponsoring state’s budget and economy against swings in international markets, or to build savings to meet future financial burdens such as pension payments. SWFs are typically funded through either commodity-based earnings, such as from a country’s natural resources sector, or by noncommodity- based resources, such as foreign exchange reserves and general taxation revenue.4 The NGPF-G is a commodity-based fund, built on Norway’s large oil reserves, while the NZSF is supported by non-commodity financing. Such concentration of wealth has made SWFs, an institutional phenomenon that began in the mid-1950s, influential actors in the global economy.5 According to the Sovereign Wealth Fund Institute, as of May 2011 there were 52 SWFs worldwide, with assets of some US$4.3 trillion.6 A recent survey by the Monitor Group, published in July 2011, put Norway’s SWF as the largest (with US$560 billion in assets), while New Zealand’s was ranked 20th (valued at US$15.8 billion).7 With SWFs’ assets expected to at least double within the next decade,8 and growing awareness of their economic clout and capacity to project state political power, international efforts to create voluntary behavioural codes for such funds have grown. The principal achievement to date is the Santiago Principles,9 which emphasise transparency, clarity, and equivalent treatment with private funds similarly operated. In addition to these issues, the socially conscious goals of some SWFs has stirred debate about the wisdom of mixing ethical investment with wealth maximisation goals, and attempting to influence corporate social and environmental behaviour.10 SWFs share several characteristics which might lead them more than private sector financiers to invest in sustainable development. Their ownership or control by a state can enmesh them in the machinery of government, and thereby render them instruments of public policy. Further, because of their sheer size and government backing, SWFs tend to have higher risk tolerances and might therefore bear investment strategies eschewed by private financiers. Thirdly, SWFs tend to have longer-term financial considerations than the private sector, which may encourage investing that is mindful of threats such as climate change. However, few states so far have obliged SWFs to invest ethically. While regulations to encourage socially responsible investment (“SRI,” as ethical investment is sometimes known) in the private sector are appearing, such as taxation incentives and corporate governance reforms, explicit duties to practice SRI have only been imposed on public financial institutions.11 The first precedents were adopted in the 1980s by some states and municipalities in the United States, which restricted government pension funds from investing in firms operating in the discriminatory milieu of South Africa12 or Northern Ireland.13 Since 2000, the SWFs of Sweden, Norway, New Zealand and France have been subject to legislative direction to invest ethically, with more comprehensive and ambitious obligations than the American precedents. Ethical investment by SWFs is controversial. Some observers believe that investment should be based only on economic and financial grounds and, especially in the case of SWFs, there is further concern that SRI could be a means for sponsoring states to insinuate their social and environmental policies globally.14 For instance, a 2009 survey of 146 asset managers having routine dealings with SWFs reported that most “did not think governments should have any influence over investment decisions despite the fact that SWFs are managing governments’ money.”15 But such concerns misunderstand the changing rationale and aims of SRI. A long-standing movement that once had few adherents,16 SRI is attracting investors who are reassessing the financial relevance of social and environmental behaviour. No longer is SRI pursued largely as a matter of ethical compulsion, as in the 1970s divestment campaign led by religious groups against South Africa’s apartheid regime,17 and their earlier admonitions against investment in tobacco, alcohol and other “sin” stocks.18 Rather, many social investors today, in both the institutional and retail sectors, take a more comprehensive view of business conduct through the lens of sustainable development. Sustainable development (or “sustainability” as the concept is sometimes known) is an ideal widely endorsed in theory as a goal of states, international bodies and businesses, and has been enshrined as an objective of the European Union treaty.19 It seeks to curb unfettered economic exploitation of nature by ensuring consumption of renewable resources within their rate of regeneration, limiting waste and pollution to the assimilative capacity of the biosphere, and conserving the biodiversity of the planet.20 Some investors recognise the financial materiality of sustainability, such as when corporate polluters create financial risks or, conversely, firms pioneer innovative environmental technologies and services.21 Although, often the nexus between environmental and financial returns is misunderstood or overlooked by financiers. For large institutional investors, including SWFs, the sustainability imperative has mostly fluently been theorised through the concept of the “universal owner.” Hawley and Williams hypothesise that institutional investors who invest widely across the market will benefit financially by taking into account the social and environmental externalities in their portfolios.22 As economy-wide investors, they should “have no interest in abetting behavior by any one company that yields a short-term boost while threatening harm to the economic system as a whole.”23 Acting as a universal investor implies that any “externality” at the level of an individual company may result in a costly “internality” for an investor’s global portfolio. Such sentiments have underpinned the proliferation of codes of conduct for SRI,24 such as the United Nations Principles for Responsible Investment (UNPRI)25 and the Equator Principles.26 Although adherence to such benchmarks is ostensibly voluntary, they have garnered many signatories, including the NGPF-G and the NZSF, and thereby helped standardise and disseminate SRI norms and practices.27 Some interesting research has begun to measure the cost of environmental externalities to universal investors. A report prepared for the UNPRI Secretariat evaluated the price of environmental damage worldwide to which the companies in a representative investment portfolio contribute, and estimated these in 2008 to be US$6.6 trillion or 11% of global GDP.28 The report expects such costs by 2050 to grow to US$28.6 trillion (18% of projected global GDP).29 The rest of this article takes up these themes by examining the SRI policies and practices of the Norwegian and New Zealand SWFs. In comparing how they attempt to reconcile their ethical and financial aspirations, the article highlights the importance of governance frameworks. While there are some salient differences in how each SWF is governed, each has, especially in their early years, focused on avoiding complicity in unethical conduct or social and environmental harm. This stance represented a rather narrow approach to ethical investment, which limited the capacity of these SWFs to promote environmentally sustainable development. More recently, both funds have begun to accept the business case for SRI, and reconceptualised ethical investment as a means of promoting long-term financial returns. But neither the NGPFG nor the NZSF is mandated to actively promote sustainable development or to seek improvements in corporations’ sustainability performance. In the future evolution of SWFs, the creation of explicit duties to invest in sustainability is perhaps the next logical step if they are to influence benignly the global economy.